Integrative medicine utilization among infertility patients - Shruti Sehgal; Ashley Dyer; Christopher Warren; Isabel Galic; Tarun Jain (BMC, 2023)
Abstract Background Previous research suggests that some women are using integrative and complementary holistic approaches to optimize their own health and treat infertility. We aimed to determine patterns of integrative medicine use among those seeking fertility optimization by 1) Characterizing patterns of integrative medicine use to increase fertility; 2) Identifying demographic predictors associated with such integrative medicine use; and 3) Exploring cultural and religious influences on use of integrative medicine. Methods Cross-sectional self-reported survey data were collected from 1460 patients presenting to an academic fertility center in Chicago, Illinois. Variables were described with univariate frequencies and proportions, unadjusted bivariate comparisons were made between patient-level factors and reported integrative modality use, and multivariable logistic regression evaluated the strength of covariate-adjusted predictors of reported integrative medicine utilization. Results 80.4% of respondents reported using at least one integrative medicine modality to treat infertility (Acupuncture: 38.5%, Yoga: 27.6%, Massage: 25.8%, Meditation: 16.7%, and Herbal supplements: 18.5%). Diet therapy was the most frequently utilized modality (74.0%) followed by body therapy (45.2%), traditional alternative medicine (42.0%), mind therapy (32.1%), and senses therapy (23.0%). Any integrative medicine modality use was 4.03 times more likely among Hindu respondents compared to participants that identified as not religious (95% CI 1.2-13.7, p < 0.026). Significant differences in specific modality use were observed by race, religious affiliation, age, income, and insurance coverage. Conclusion Most infertility patients in our study reported using at least one integrative medicine modality to help them conceive. Utilization was associated with age of participant, religious affiliation, annual income, and insurance coverage. Further research is needed to assess the impact of integrative medicine utilization on patient quality of life and outcomes.